Paying Primary Health Care Centers for Performance in Rwanda - Basinga, Paulin; Gertler, Paul J.; Soucat, Agnes L.B.; Binagwaho, Agnes; Soucat, Agnes L.B.; Sturdy, Jennifer R.; Vermeersch, Christel M.J. (World Bank, Washington, DC, 2014)
Paying for performance (P4P) provides financial incentives for providers to increase the use and quality of care. P4P can affect health care by providing incentives for providers to put more effort into specific activities, and by increasing the amount of resources available to finance the delivery of services. This paper evaluates the impact of P4P on the use and quality of prenatal, institutional delivery, and child preventive care using data produced from a prospective quasi-experimental evaluation nested into the national rollout of P4P in Rwanda. Treatment facilities were enrolled in the P4P scheme in 2006 and comparison facilities were enrolled two years later. The incentive effect is isolated from the resource effect by increasing comparison facilities' input-based budgets by the average P4P payments to the treatment facilities. The data were collected from 166 facilities and a random sample of 2158 households. P4P had a large and significant positive impact on institutional deliveries and preventive care visits by young children, and improved quality of prenatal care. The authors find no effect on the number of prenatal care visits or on immunization rates. P4P had the greatest effect on those services that had the highest payment rates and needed the lowest provider effort. P4P financial performance incentives can improve both the use of and the quality of health services. Because the analysis isolates the incentive effect from the resource effect in P4P, the results indicate that an equal amount of financial resources without the incentives would not have achieved the same gain in outcomes.